Studi Keberadaan Escherichia coli dan Staphylococcus aureus pada Pangan Tradisional Lawar Putih di Destinasi Wisata Pura Uluwatu - Agitian, Ezra; Darmayanti, Luh Putu Trisna; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
Lawar is a traditional Balinese food made from vegetables, minced meat, and grated coconut with Balinese spices. Most of the processed lawar use meat as the main raw material. On the other hand, meat is one of the foodstuffs that have high water content and a neutral pH which is prone to contamination with Escherichia coli and Staphylococcus aureus bacteria. The aim of this study was to determined microbial contamination of Balinese food pork and sanitation practices in several restaurants that sell pork lawar in the tourist destination area Uluwatu Temple. This study used simple random sampling and survey techniques. The results of this study served in data tables and the data ware analyzed descriptively. Parameters observed were total microbes, coliform, E. coli, and S. aureus. The results showed that 100% of pork lawar met the requirements for the total microbes of processed meat with heat treatment (<1x106 cfu/g), all pork lawar were positive for coliforms, 87.5% pork lawar did not met the requirements processed meat with heat treatment for E. coli (<1x102 cfu/g), and 100% of pork lawar had met the requirements processed meat with heat treatment for S. aureus (<1x102 cfu/g). Sanitation practices at the pork lawar restaurant in the tourist area Uluwatu Temple include traders bought raw materials at the local market, 50% of raw materials are directly processed, 50% of raw materials did not use directly, 50% of producers processed lawar in the morning, 62.5% of traders took lawar without wearing gloves, cleanliness of traders and personal hygiene were still not good.